(untitled) (Itinera, 2022)
The purpose of this essay is to advocate the ideas of Wilhelm Worringer, John Dewey, and Nelson Goodman on the roles of perception, empathy, emotion, and enjoyment in aesthetic experience. I will attempt to do this by offering a novel interpretation of some of these thinkers’ insights from a biological perspective. To this end, I will consider the following questions. What is an aesthetic experience? Does such a thing exist at all? If yes, is there a correlation between the concept of the aesthetic and perception? Is it possible, then, to find a biological basis for aesthetic experience? My argument is that a fresh analysis of the aesthetics of Worringer, Dewey, and Goodman, in light of some of the discoveries and theories of the cognitive neurosciences – such as the biological correlations of emotions, the “as-if-body-loop” theory, the discovery of mirror neurons, and the phenomenon of embodied simulation – may provide a contribution to longstanding philosophical problems relating to the nature of aesthetic experience.